Elucidation of basic mechanisms of flavokawin B inhibitory effects on the growth of selected cancer and transformed normal cell lines - Umar, Nasir Tsafe (2008)
Flavokawin B (FNB) is a hydroxychalcone isolated from a local plant species,Alpinia zerumbet of the Zingiberaceae family. It has been shown to have antioxidant and pro-immune properties. The aim of the present study was to assess the basic growth inhibitory mechanisms of FNB, on 21 cell lines, comprising tumour and transformed cell lines. The cells were treated with FNB at 0.1, 1, 3, 10, 30 and 100 μM. Over 3 to 4 days exposure, FNB selectively inhibited the growth of all the cell lines. Tumour cells were more sensitive to FNB than normal cells. MTT cytotoxicity assay was then conducted in order to assess the cytotoxic-indices of FNB. Caco-2, CEM-SS, MCF-7, T-47D and U87MG were found to be the five most sensitive cell lines, with IC50 values of 6.53 ± 0.81, 2.00 ± 0.41, 7.67 ± 0.71, 8.67 ± 1.40 and 14.00 ± 3.00 μM respectively. Tamoxifen (TMX) was used as a positive control for the 5 cell lines, with all the IC50 values found to be comparable to that of FNB. Cell survival analysis confirmed very significant patterns of FNB efficacy (P<0.001 - P<0.05), in comparison to the untreated/negative controls in all the 5 cell lines. Apoptosis induction was then assessed by life-culture morphology in all the 21 cell lines, out of which 9 indicated apoptosis induction. Nucleoprotein fluorescence analysis was carried out in order to quantify and establish apoptotic frequencies. Combined image captures were used to analyse the apoptotic effects. FNB was found to induce apoptosis at the IC50 concentrations in 9 of the 21 cell lines. The most significant FNB-induced apoptotic frequencies compared to the untreated controls, were found at 70.67 ± 7.51% (P<0.01), 68.17± 6.81% (P<0.01), 49.33 ± 7.32% (P<0.01), 57.5 ± 4.82% (P<0.01) and 52.83 ± 3.62% (P<0.001), for the Caov- 3, CEM-SS, CHO, HL-60 and MDA-MB-468 cell lines, respectively. The maximal apoptotic frequency effect induced by FNB was on the Caov-3 cell line, which was more significant than etoposide (ETS) positive control (P<0.05). Apoptosis induction was confirmed only in the 5 most significant (P<0.01) cell lines, using agarose gel electrophoresis for DNA-laddering. The effect of FNB on oestrogen metabolism at IC50 concentrations, was tested using radioisotope enzymatic assays for oestrone sulphatase (E1STS) and oestradiol-17b hydroxysteroid dehydrogenase (oestrone - oestradiol, E2HD), on four selected human breast cancer cell lines (MCF-7, T-47D, MDA-MB-231, MDA-MB-468). FNB had significant inhibitory effects on the E1STS enzyme in the MCF-7 and T-47D cell lines, with 26.41 ± 0.69% (P < 0.01) and 18.53 ± 1.21% (P < 0.05), respectively at IC50 levels. FNB also significantly inhibited the E2HD enzyme in the T-47D cell line (36.40 ± 1.70%,P < 0.01). Confirmatory assays using the E1STS and E2HD ELISA kits were conducted on the MCF-7 and T-47D cell lines. Similar inhibitory effects of FNB on both enzymes were found in the MCF-7 and T-47D cell lines. On the other hand,FNB stimulated both enzymes in the non-oestrogen dependent cell lines, MDA-MB 231 and MDA-MB-468. Finally, genotoxicity study was conducted in order to establish a safety profile of FNB in the CHO normal cell line, using ethylmethanesulphonate (EMS) as a positive control. Antigenotoxicity was assayed using a combination of FNB and EMS. The results showed an insignificant FNB clastogenicity (P>0.05, at 45 μM) and a significant FNB anti-clastogenicity (P<0.05,at 45 μM), in the CHO cells. In conclusion, the overall cytotoxicity, selectivity, cell survival, apoptotic, anti-oestrogenic, non-genotoxic and anti-genotoxic properties of flavokawin B (which are comparably better than TMX, ETS and EMS), forms the basic inhibitory mechanisms, which make this compound potentially an interesting anti-neoplastic agent.